Honey: an immunomodulatory agent for disorders of the skin - McLoone, Pauline; Warnock, Mary; Fyfe, Lorna (My University, 2016)
Studies have shown that honeys from around the world can inhibit the growth of a range of dermatologically important microbes. As well as reports of the antimicrobial properties of honey, a number of recent in vitro and in vivo studies suggest that honey is able to modulate immunological parameters related to the skin immune system. Paradoxically, both immune-stimulatory and anti-inflammatory effects have been observed. In this review, scientific research investigating the immunomodulatory properties of honeys from around the world, in relation to disorders of the skin, is evaluated. Whilst there is sufficient evidence to suggest that honey does indeed have immunomodulatory properties, which may at least partially explain the ability of honey to promote the healing of wounds, there are still gaps in the scientific knowledge and literature. More research is necessary for a more complete understanding of the immune modulating properties of honey and to enable the utilisation of honey as an immune-modulating agent in dermatology
Keywords: honey; immunomodulatory; skin disorders; wound healing